Surface treatment method of quantum dots and surface treatment apparatus
By using organosilicon compounds with coordinating and reactive substituents on the surface of quantum dots for photopolymerization, the instability and compatibility issues of quantum dots were solved, and efficient and stable wavelength conversion materials were prepared.
Patent Information
- Application Number
- CN202180080828.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-07
- Filing Date
- 2021-11-30
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2041-11-30
AI Technical Summary
Quantum dots, due to their small particle size and large surface area, are prone to instability, leading to deterioration of their fluorescence emission properties. Furthermore, their poor compatibility with silicone resin materials affects the color uniformity and luminescence uniformity of displays. Existing covering methods cannot effectively solve these problems.
By continuously supplying a solution of organosilicon compounds with coordinating and reactive substituents to the surface of quantum dots and covering it with a photopolymerization reaction, and by using a reaction channel of a light-transmitting material for processing, the uniformity and stability of the coverage are ensured.
Even during large-volume solution processing, it can stably coat the quantum dot surface, improving its stability and compatibility with resin materials, and providing a highly reliable wavelength conversion material.
Smart Images

Figure CN116547232B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a surface treatment method and apparatus for quantum dots. Background Technology
[0002] Semiconductor crystal particles with a diameter of nanometers are called quantum dots. Because excitons generated through light absorption are confined to a nanometer-sized region, the energy levels of the semiconductor crystal particles become discrete, and their band gap varies with particle size. Due to these effects, quantum dots exhibit higher brightness and efficiency in fluorescence emission compared to conventional phosphors, and their emission is sharper.
[0003] Furthermore, due to the characteristic that the band gap varies with its particle size, quantum dots possess the ability to control the emission wavelength, making their application as wavelength conversion materials for solid-state lighting or displays highly anticipated. For example, by using quantum dots as wavelength conversion materials in displays, it is possible to achieve a wider color gamut and lower power consumption than conventional phosphor materials.
[0004] As a method for mounting quantum dots as wavelength conversion materials, a method has been proposed that disperse quantum dots in a resin material, laminate the quantum dot-containing resin material onto a transparent film to form a wavelength conversion film, and then mount it into a backlight unit (Patent Document 1). Furthermore, a method has been proposed that uses quantum dots as a color filter material, and by having the quantum dots absorb blue monochromatic light from the backlight unit and emit red or green light, it can be applied to image elements that utilize both color filter materials and wavelength conversion materials to achieve high efficiency and excellent color reproduction (Patent Document 2). Existing technical documents Patent documents
[0005] Patent Document 1: Japanese Patent Publication No. 2013-544018 Patent Document 2: Japanese Patent Application Publication No. 2017-21322 Patent Document 3: Japanese Patent No. 5356318 Patent Document 4: Japanese Patent No. 6592540 Patent Document 5: Japanese Patent No. 5900720 Summary of the Invention The technical problem to be solved by the present invention
[0006] However, due to the nanoscale size of quantum dots, their specific surface area is relatively large. Consequently, their surface energy is high and their surface is highly active, making them prone to instability. Surface defects such as dangling bonds or oxidation reactions easily form on the quantum dot surface, causing degradation of fluorescence luminescence properties. This is particularly problematic for cadmium-free quantum dots or perovskite quantum dots. Previously obtained quantum dots are known to have this stability-related issue, and their luminescence properties can deteriorate due to heat, humidity, or photoexcitation, thus adversely affecting devices. Furthermore, typical quantum dots are hydrophobic, resulting in poor compatibility with polar silicone and other resin materials, sometimes leading to aggregation, which is also a serious problem.
[0007] Because the light-emitting properties of quantum dots change over time or agglomerate, defects such as uneven color, uneven light emission, or defective pixels can occur in displays, improving the stability of quantum dots is an important issue.
[0008] To address this issue, methods have been explored for covering the surface of quantum dots with polymers or inorganic oxides (Patent Documents 3 and 4), or for improving the stability of quantum dots by using a barrier membrane with low oxygen or moisture permeability (Patent Document 5).
[0009] However, in the process of covering the quantum dot surface to improve stability as described in Patent Documents 3 and 4, there is a problem that the luminescence properties of the quantum dots cannot be maintained, leading to property degradation. Furthermore, regarding the stabilization using a barrier film as described in Patent Document 4, there is also a problem of degradation due to the diffusion of oxygen or water vapor from the film's end face. Furthermore, although thinning of wavelength conversion materials is required in mobile applications such as tablets or smartphones, the use of barrier films limits the thinning of wavelength conversion materials. Furthermore, in applications such as color filters or μLEDs, the mounting method makes it difficult to use barrier films, thus hindering applicability in applications other than those requiring films.
[0010] Therefore, the inventors of this application have discovered that a method for obtaining highly reliable and stable quantum dots by covering the surface of quantum dots under mild conditions that do not cause degradation of the quantum dots involves substituting the surface of the quantum dots with ligands having reactive substituents and then fixing an organosilicon compound having substituents that can polymerize with the reactive functional group onto the surface of the quantum dots through a photopolymerization reaction. However, when this method is carried out in a container such as a flask containing a solution (so-called batch processing), if the amount of solution is increased to increase the throughput, it is obvious that incomplete surface coverage will not be achieved.
[0011] The present invention was made in view of the above-mentioned problems, and its object is to provide a surface treatment method for quantum dots and a surface treatment apparatus for use in the surface treatment method. The surface treatment method for quantum dots can stably utilize organosilicon compounds to cover the surface of quantum dots even when using a large amount of solution for surface treatment, thereby obtaining quantum dots with excellent stability at high productivity, and further providing wavelength conversion materials with improved compatibility between quantum dots and resin materials and high properties and reliability. Technical means to solve technical problems
[0012] The present invention is made to achieve the above-mentioned objective. The present invention provides a surface treatment method for quantum dots, wherein a solution of a ligand containing a coordinating substituent and a reactive substituent, wherein the coordinating substituent is coupled to the quantum dots on the surface and an organosilicon compound is continuously supplied to a reaction channel made of a light-transmitting material, while the reaction channel is irradiated with light, so that the organosilicon compound and the reactive substituent undergo a photopolymerization reaction, thereby using the organosilicon compound to cover the surface of the quantum dots.
[0013] Based on this quantum dot surface treatment method, even when using a large amount of solution for surface treatment, it is possible to stably cover the surface of quantum dots with organosilicon compounds, thereby providing highly reliable wavelength conversion materials.
[0014] At this time, the surface treatment method for quantum dots can be as follows: that is, the coordinating substituent is any one or more of amino, thiol, carboxyl, phosphine, and quaternary ammonium salt.
[0015] Such coordinating substituents exhibit excellent coordination with the quantum dot surface, effectively suppressing ligand detachment from the quantum dot, and can react stably and efficiently with organosilicon compounds.
[0016] At this time, the surface treatment method for quantum dots can be as follows: that is, the reactive substituent is any one or more of vinyl, acryloyl, methacryl, thiol, epoxy, and oxetane.
[0017] Such reactive substituents can react stably and efficiently with organosilicon compounds.
[0018] At this point, a surface treatment method for quantum dots can be provided where the reaction channel is tubular, and the concentration of the solution and / or the diameter of the reaction channel are adjusted in such a way that the transmittance of the light transmitted to the reaction channel is at least 0.1%.
[0019] Therefore, it is possible to use organosilicon compounds for coating more stably.
[0020] Furthermore, the present invention provides a surface treatment apparatus for quantum dots, comprising: a solution supply unit capable of adjusting the supply flow rate of a solution containing quantum dots and a reactive compound that reacts with the surface of the quantum dots; a light source irradiating light for causing the quantum dots to undergo a photoreaction with the reactive compound; and a reaction conduit formed of a material that transmits light irradiated by the light source, wherein the quantum dots in the solution supplied by the solution supply unit undergo a photoreaction with the reactive compound.
[0021] According to such a quantum dot surface treatment device, even when using a large amount of solution for surface treatment, it is possible to stably cover the surface of quantum dots with organosilicon compounds. Invention Effects
[0022] As described above, the quantum dot surface treatment method according to the present invention can stably utilize organosilicon compounds to cover the surface of quantum dots even when using a large amount of solution for surface treatment, thereby providing wavelength conversion materials with high properties and reliability. Furthermore, the quantum dot surface treatment apparatus according to the present invention can stably utilize organosilicon compounds to cover the surface of quantum dots even when using a large amount of solution for surface treatment. Attached Figure Description
[0023] Figure 1 A specific example of the surface treatment apparatus for quantum dots of the present invention is shown. Detailed Implementation
[0024] The present invention will now be described in detail, but the invention is not limited thereto.
[0025] As described above, the inventors of this application have discovered a method for manufacturing a polymer containing quantum dots. This method enables the coating of quantum dot surfaces under mild conditions that have minimal impact on luminescence behavior such as quantum efficiency or emission wavelength and do not cause quantum dot degradation. This method can efficiently manufacture stable quantum dots with high reliability. The manufacturing method of the polymer containing quantum dots involves a polymerization step after a ligand exchange step. In the ligand exchange step, a solution containing dispersed quantum dots is mixed with a compound containing ligands with reactive substituents, so that the ligands with reactive substituents are located on the outermost surface of the quantum dots. In the polymerization step, an organosilicon compound containing substituents that can polymerize with the reactive substituents is added to the solution containing the quantum dots with reactive substituents located on the outermost surface and mixed to polymerize the quantum dots with the organosilicon compound, thereby synthesizing the polymer containing quantum dots.
[0026] However, if the solution volume is increased and the reaction is carried out in order to increase the throughput in this method, new problems will obviously arise, such as the inability to completely cover the surface. Therefore, there is a need to improve the properties and reliability of quantum dots as wavelength conversion materials by improving their stability and compatibility with resin materials, and to improve productivity by enabling mass production.
[0027] To address this issue, the inventors of this application conducted in-depth research and discovered that in the polymerization process, if the solution volume is around tens of milliliters, processing within a flask is not problematic. However, if the solution volume reaches several hundred milliliters or more, the unevenness of the photopolymerization reaction within the solution prevents uniform coating of the organosilicon compound onto the quantum dot surface, leading to a decrease in the stability of the quantum dots or their compatibility with the resin. This is because the quantum dots themselves strongly absorb the UV light used for the photoreaction.
[0028] Therefore, it has been found that by continuously supplying a solution containing ligands having coordinating and reactive substituents to quantum dots on the surface via the coordinating substituents and an organosilicon compound that can polymerize with the reactive substituents through a conduit made of a material that transmits light for photoreaction, a photopolymerization reaction can be carried out simultaneously. Even when processing large quantities of solution, a stable and uniform coating of organosilicon compound on the surface of the quantum dots can be achieved, and high productivity can be obtained.
[0029] That is, the inventors of this application have discovered a surface treatment method for quantum dots, wherein a solution of a ligand containing a coordinating substituent and a reactive substituent, wherein the coordinating substituent is located on the surface of the quantum dots and an organosilicon compound is continuously supplied to a reaction channel made of a light-transmitting material, while the reaction channel is irradiated with light, causing the organosilicon compound and the reactive substituent to undergo a photopolymerization reaction, thereby using the organosilicon compound to cover the surface of the quantum dots. Through this surface treatment method for quantum dots, even when using a large amount of solution for surface treatment, the surface of the quantum dots can be stably covered with organosilicon compounds, and a highly reliable wavelength conversion material can be provided, thus completing the present invention.
[0030] Furthermore, the inventors of this application have discovered a surface treatment apparatus for quantum dots, comprising: a solution supply unit capable of adjusting the supply flow rate of a solution containing quantum dots and a reactive compound that reacts with the surface of the quantum dots; a light source irradiating light for causing the quantum dots to undergo a photoreaction with the reactive compound; and a reaction channel formed of a material that transmits light irradiated by the light source, which internally causes the quantum dots in the solution supplied by the solution supply unit to undergo a photoreaction with the reactive compound. With this surface treatment apparatus for quantum dots, even when surface treatment is performed using a large amount of solution as a raw material, a stable surface coating of quantum dots using an organosilicon compound can be achieved, thus completing the present invention.
[0031] Furthermore, although the quantum dot surface treatment method and quantum dot surface treatment apparatus of the present invention were invented to solve problems, especially when processing large amounts of solution, it is clear that the surface coating of quantum dots can also be stably achieved using organosilicon compounds when processing small amounts of solution. Of course, the present invention is not limited by the amount of solution being processed.
[0032] The present invention will now be described in detail.
[0033] First, a quantum dot (hereinafter, sometimes referred to as "quantum dot polymer") with a surface covered by an organosilicon compound, obtained by the surface treatment method of the quantum dot (hereinafter, sometimes referred to as "QD") of the present invention, will be described.
[0034] [Polymers with sub-dot content] For the quantum dot-containing polymers obtained by the quantum dot surface treatment method of the present invention, the surface of the quantum dots is covered with an organosilicon compound (sometimes also called polysiloxane).
[0035] (Quantum dot) There are no particular restrictions on the composition of quantum dots; the quantum dots can be selected according to the purpose. Examples of quantum dot compositions include group II-IV semiconductors, group III-V semiconductors, group II-VI semiconductors, group I-III-VI semiconductors, group II-IV-V semiconductors, group IV semiconductors, perovskite semiconductors, etc. Furthermore, quantum dots can have only a core or a core-shell structure. The particle size of the quantum dots can be appropriately selected according to the target wavelength range.
[0036] Specifically, examples of nuclear materials include CdSe, CdS, CdTe, InP, InAs, InSb, AlP, AlAs, AlSb, ZnSe, ZnS, ZnTe, Zn3P2, GaP, GaAs, GaSb, CuInSe2, CuInS2, CuInTe2, CuGaSe2, CuGaS2, CuGaTe2, CuAlSe2, CuAlS2, CuAlTe2, AgInSe2, AgInS2, AgInTe, AgGaSe2, AgGaS2, AgGaTe2, PbSe, PbS, PbTe, Si, Ge, graphene, CsPbCl3, CsPbBr3, CsPbI3, CH3NH3PbCl3, and their mixed crystals or substances with added dopants.
[0037] Examples of shell materials in the case of core-shell structures include ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, AlSb, BeS, BeSe, BeTe, MgS, MgSe, MgTe, PbS, PbSe, PbTe, SnS, SnSe, SnTe, CuF, CuCl, CuBr, CuI, and their mixed crystals.
[0038] Furthermore, there are no particular limitations on the shape of the quantum dots; they can be freely chosen according to the purpose. The shape of the quantum dots can be spherical, cubic, or rod-shaped. In addition, there are no particular limitations on the average particle size of the quantum dots, but it is desirable to be below 20 nm. If the average particle size is within this range, a stable quantum size effect can be obtained, resulting in high luminescence efficiency and easy control of the band gap caused by particle size. Moreover, the particle size of the quantum dots can be measured by examining particle images obtained using a transmission electron microscope (TEM), and calculated based on the average of the maximum diameter (Feret diameter) of more than 20 particles in a certain direction. Of course, the method for determining the average particle size is not limited to this; other methods can also be used.
[0039] The quantum dots of the present invention have ligands on their surface, said ligands having coordinating substituents and reactive functional groups. There are no particular restrictions on the structure of the ligands, but substances with a linear chain length of 20 or less are preferred. With such ligands, the amount of ligands coordinated to the surface of the quantum dots becomes sufficient, and the amount that can subsequently polymerize and interact with organosilicon compounds also becomes sufficient.
[0040] The coordinating substituent is preferably any one or more of amino, thiol, carboxyl, phosphine, and quaternary ammonium salts. Such coordinating substituents exhibit excellent coordination with the quantum dot surface, effectively inhibiting ligand detachment from the quantum dots, and enabling stable and efficient reactions with organosilicon compounds.
[0041] The reactive substituent is preferably any one or more of vinyl, acryloyl, methacryl, thiol, epoxy, and oxetane. Such reactive substituents can react stably and efficiently with organosilicon compounds.
[0042] In addition, the surface of quantum dots may also contain ligands other than those mentioned above. There are no particular limitations on the types of such ligands, but examples include oleic acid, stearic acid, palmitic acid, myristic acid, lauric acid, decanoic acid, octanoic acid, oleylamine, stearylamine, dodecylamine, decylamine, octylamine, octadecyl mercaptan, hexadecyl mercaptan, tetradecyl mercaptan, dodecyl mercaptan, decyl mercaptan, octyl mercaptan, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, tributylphosphine, and tributylphosphine oxide.
[0043] (organosilicon compounds) The organosilicon compound (polysiloxane) used to cover the surface of the quantum dots is not particularly limited as long as it has polymerizable substituents that can react with ligands having the aforementioned reactive substituents. However, from the perspective of the compatibility of the quantum dots coordinated with the ligands in hydrophobic solvents and the uniform reaction before polymerization, the organosilicon compound is preferably in liquid or oil form. It is acceptable as long as it has at least one polymerizable substituent on either or both of the molecular chain ends and side chains. Vinyl-modified silicone oils, acrylic-modified silicone oils, methacrylic acid-modified silicone oils, etc., are preferred as such organosilicon compounds. Multiple modified silicone oils can be mixed as long as they do not cause aggregation or other issues from a compatibility perspective; there are no particular limitations.
[0044] (Wavelength conversion materials of polymers with content sub-dots) The wavelength conversion material of the present invention is a resin composition containing a polymer containing the sub-dots of the present invention dispersed in a resin. The resin material is not particularly limited, but preferably a resin material that does not cause polymer aggregation of the sub-dots or deterioration of fluorescence efficiency; examples include silicone resins, acrylic resins, epoxy resins, urethane resins, and fluororesins. To improve the fluorescence efficiency of the wavelength conversion material, these materials are preferably substances with high transmittance, and particularly preferably substances with a transmittance of 70% or more. Furthermore, the form of the wavelength conversion material of the present invention is not particularly limited; examples include wavelength conversion films in which the polymer containing the sub-dots is dispersed in a resin.
[0045] [Surface Treatment Apparatus] First, referring to the accompanying drawings, the quantum dot surface treatment apparatus of the present invention, used in the surface treatment method for obtaining quantum dots (polymers containing quantum dots) covered with organosilicon compounds as described above, will be described.
[0046] Figure 1 A specific example of the surface treatment apparatus for quantum dots of the present invention is shown in the figure. Figure 1 The quantum dot surface treatment apparatus 10 shown includes at least a light source 1, a reaction conduit 2, and a solution supply unit 3. The solution supply unit 3 is capable of adjusting the supply flow rate of a solution containing quantum dots and a reactive compound that reacts with the surface of the quantum dots. The light source 1 irradiates light to cause a photoreaction between the quantum dots and the reactive compound in the solution. The reaction conduit 2, inside which the quantum dots in the solution supplied by the solution supply unit 3 undergo a photoreaction with the reactive compound, is formed of a material that transmits light irradiated by the light source 1. Using such a surface treatment apparatus, even when using a large amount of solution for surface treatment, a stable surface coating of quantum dots using an organosilicon compound can be achieved.
[0047] In addition, such as Figure 1 As shown, the structure can be as follows: a container 6B containing a pre-reaction solution 6A comprising quantum dots and reactive compounds is connected to a reaction pipeline 2 via a solution supply pipe 4 and a solution supply unit 3. Downstream of the reaction pipeline 2, it is connected to a container 7B containing a post-reaction solution 7A via a solution discharge pipe 5 that discharges the post-reaction solution, but this is not a limitation. For example, there can be more than one reaction pipeline 2, or multiple reaction pipelines 2 parallel to the light source 1. The pre-reaction solution 6A can be a solution premixed with quantum dots or reactive compounds, or the quantum dots or reactive compounds can be supplied separately and mixed again before being supplied to the reaction pipeline 2. In this case, multiple solution supply units can be set up separately.
[0048] As light source 1, any light source capable of illuminating the quantum dots and reactive compounds to induce a photopolymerization reaction is acceptable. There are no particular limitations on the wavelength, intensity, or irradiation area of the light used for the photopolymerization reaction; these can be appropriately modified according to the conditions required for the target reaction. For example, a light source capable of illuminating UV light could be used.
[0049] The material used to form the reaction channel 2 is not particularly limited as long as it is capable of transmitting light used for the photopolymerization reaction irradiated by the light source 1. For example, when using a light source that irradiates UV light, quartz material with high transmittance to UV light is particularly preferred. The length of the reaction channel 2 or the dimensions of the light transmission direction can be appropriately set within a range that allows sufficient light to reach the solution inside. If the transmittance of light transmitted through the reaction channel 2 is at least 0.1%, sufficient light can be irradiated onto the solution, enabling a more stable and uniform reaction. However, as described below, since the transmittance of light in the reaction channel 2 depends not only on the material of the reaction channel 2 but also on the concentration of quantum dots or reactive compounds in the solution, it can be set, for example, in such a way that at least 0.1% of the light incident on the reaction channel 2 is transmitted by setting the solution concentration according to the diameter of the reaction channel, or conversely, setting the diameter of the reaction channel according to the concentration of the solution.
[0050] There are no particular restrictions on the solution supply pipe 4 and the solution discharge pipe 5, as long as they are chemically stable relative to the solution in which the reaction takes place. Examples include Teflon (registered trademark) pipes, silicone pipes, and urethane pipes.
[0051] Furthermore, the solution supply unit 3, which is capable of adjusting the supply flow rate, can be appropriately selected from tubular pumps or plunger pumps, or devices that use flow meters to regulate inactive gases and pressurize them, depending on the amount of liquid being transported or the diameter of the solution supply pipe 4 and the solution discharge pipe 5.
[0052] [Preparation method of polymers containing sub-dots] Next, a method for preparing a polymer containing quantum dots with a surface treatment including the quantum dots of the present invention will be described.
[0053] (Preparation of quantum dots) First, prepare the quantum dots as described above. There are no particular limitations on the method for manufacturing quantum dots.
[0054] (ligand exchange) Next, for the prepared quantum dots, ligands with coordinating and reactive substituents are positioned on the surface of the quantum dots via the coordinating substituents. For example, ligand exchange can be performed by dispersing quantum dots with ligands containing long-chain hydrocarbons in a hydrophobic solvent and mixing them with ligands with coordinating and reactive substituents. In the ligand exchange reaction, conditions such as the amount added, heating temperature, time, and light irradiation can be appropriately varied depending on the type of ligand. Furthermore, if the remaining ligands or detached ligands after ligand exchange may affect the photopolymerization of organosilicon compounds such as modified silicone oil, it is preferable to purify them first.
[0055] (Surface treatment of quantum dots) Next, quantum dots with coordinating and reactive substituents obtained through ligand exchange as described above, which are coordinated to the surface by the coordinating substituents, are dispersed in a solvent. An organosilicon compound, such as modified silicone oil, with substituents capable of photopolymerization, is then added and mixed to obtain a solution. Examples of solvents include pentane, hexane, octane, benzene, toluene, and octadecene, but the solvent is not limited to these.
[0056] Furthermore, it is preferable to add a photopolymerization initiator to the above-mentioned solution. A photopolymerization initiator, quantum dots with ligands having polymerizable reactive substituents, and an organosilicon compound with polymerizable substituents can be mixed, stirred, and uniformly mixed in a hydrophobic solvent, and then irradiated with light such as ultraviolet light to rapidly obtain a photopolymer. By carrying out the polymerization reaction through light irradiation in this way, a polymer containing quantum dots with the surface of the quantum dots covered by an organosilicon compound can be obtained.
[0057] Examples of photopolymerization initiators from the Irgacure (Irgacure (registered trademark)) series sold by IGM Resins include Irgacure 290, Irgacure 651, Irgacure 754, Irgacure 184, Irgacure 2959, Irgacure 907, Irgacure 369, Irgacure 379, Irgacure 819, and Irgacure 1173. Additionally, examples from the Darocure (Darocure (registered trademark)) series include TPO and Darocure 1173. Other initiators may also include known free radical polymerization initiators or cationic polymerization initiators. The content of the photopolymerization initiator is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight, relative to 100 parts by weight of the added modified silicone oil.
[0058] In this invention, a solution containing quantum dots with ligands having coordinating and reactive substituents on their surfaces and an organosilicon compound capable of polymerizing with the reactive substituents is continuously supplied to a reaction channel made of a material that transmits light for photopolymerization, thereby initiating a reaction. For such surface treatment, it is possible to use... Figure 1 The surface treatment apparatus shown is used for this purpose. Therefore, even when processing large volumes of solution in a scaled-up reaction system, photopolymerization can be carried out uniformly throughout the solution, and the surface of quantum dots can be uniformly covered with organosilicon compounds. Even when increasing the amount of solution used in the polymerization process, the surface of quantum dots can be uniformly covered with organosilicon compounds by improving the stability of the quantum dots or suppressing the decrease in compatibility with the resin, thus achieving high productivity.
[0059] Furthermore, the solution concentration and the size of the channel are preferably adjusted in such a way that the transmittance of light transmitted through the reaction channel from the light-irradiating surface to the opposite side is at least 0.1%. By setting such conditions, it is ensured that the reaction occurs uniformly in the light-irradiated area. It is preferable to make the reaction channel into a tubular shape, and the transmittance can be adjusted by adjusting the solution concentration and / or the diameter of the reaction channel. As methods for determining the transmittance, there are methods that measure it directly on the channel, methods that measure the absorbance (transmittance) at the wavelength of the light source based on the measurement of the visible and ultraviolet absorption spectrum of the reaction solution, and methods that calculate the concentration and the channel diameter according to Lambert-Beer's law A = αLC, (A: absorbance, α = absorption coefficient, L: light path length, C: concentration).
[0060] (Manufacturing of wavelength conversion materials from polymers with content sub-dots) There are no particular limitations on the manufacturing method of wavelength conversion materials. Wavelength conversion films can be produced by processing them into sheets and then curing them, resulting in a polymer containing sub-dots dispersed in a resin. For example, a polymer containing sub-dots can be dispersed in an acrylic resin, the resin composition can be coated onto a transparent film such as PET or polyimide, cured, and then laminated to obtain the wavelength conversion material. The coating of the transparent film can be done using spraying or inkjet methods, spin coating, or rod coating.
[0061] There are no particular limitations on the method for curing the resin composition. For example, it can be cured by heating a film coated with the resin composition at 60°C for 2 hours, followed by heating at 150°C for 4 hours. In addition, the resin composition can be cured by photopolymerization, and other methods can be modified as appropriate according to its application. Example
[0062] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto.
[0063] In the examples and comparative examples described below, InP / ZnSe / ZnS core-shell quantum dots were used as the quantum dot materials. For the evaluation of the fluorescence properties of the quantum dots (polymers containing quantum dots) obtained by surface treatment, a quantum efficiency measurement system (QE-2100) manufactured by Otsuka Electronics Co., Ltd. was used to measure the emission wavelength, fluorescence emission half-width, and fluorescence efficiency (internal quantum efficiency) of the quantum dots at an excitation wavelength of 450 nm.
[0064] [Comparative Example 1] (Quantum dot nucleosynthesis process) Add 0.23 g (0.9 mmol) of palmitic acid, 0.088 g (0.3 mmol) of indium acetate, and 10 mL of 1-octadecene to a flask. Heat and stir at 100 °C under reduced pressure, degassing for 1 hour while dissolving the raw materials. Then, purge the flask with nitrogen, add 0.75 mL (0.15 mmol) of a solution of tris(trimethylsilyl)phosphine and trioctylphosphine adjusted to 0.2 M, and heat to 300 °C. The solution changes color from yellow to red, confirming the formation of nuclei.
[0065] (Quantum dot shell synthesis process) Next, 2.85 g (4.5 mmol) of zinc stearate and 15 mL of 1-octadecene were added to another flask. The mixture was heated and stirred at 100 °C under reduced pressure, and degassed for 1 hour while dissolving the stearate to prepare a 0.3 M zinc stearate-octadecene solution. 3.0 mL (0.9 mmol) of this solution was added to the nucleosynthesis reaction solution and cooled to 200 °C. Then, 0.474 g (6 mmol) of selenium and 4 mL of trioctylphosphine were added to another flask and heated to 150 °C to dissolve the selenium-trioctylphosphine solution, thus preparing a 1.5 M selenium-trioctylphosphine solution. The reaction solution after the nucleosynthesis step, cooled to 200 °C, was heated to 320 °C over 30 minutes, while adding 0.1 mL of the selenium-trioctylphosphine solution each time, for a total of 0.6 mL (0.9 mmol). The solution was maintained at 320 °C for 10 minutes and then cooled to room temperature. Add 0.44 g (2.2 mmol) of zinc acetate and heat and stir at 100 °C under reduced pressure until dissolved. Purge the flask with nitrogen again and heat to 230 °C. Add 0.98 mL (4 mmol) of 1-dodecylthiol and maintain the temperature for 1 hour. Cool the resulting solution to room temperature to prepare a solution of core-shell quantum dots composed of InP / ZnSe / ZnS.
[0066] (Ligand exchange process) 2-Propylene-1-thiol (TOKYO CHEMICAL INDUSTRY CO.,LTD) was used as the ligand with both coordinating and reactive substituents. As a ligand exchange reaction, the solution after the shell synthesis step, cooled to room temperature, was heated to 60°C, and 0.08 mL (1.0 mmol) of 2-propenne-1-thiol was added, followed by stirring for 1 hour. After the reaction was complete, the solution was cooled to room temperature, ethanol was added to precipitate the reaction solution, and centrifugation was performed to remove the supernatant. The same purification process was repeated, and the solution was dispersed in toluene to prepare a quantum dot solution with ligands with reactive substituents coordinated on the outermost surface.
[0067] (Surface treatment process / Synthesis of polymers with high content of sub-dots) 20 mL of the quantum dot toluene solution (QD concentration 7% by mass) after the ligand exchange process was added to a flask pre-purged with nitrogen. For every 100 parts by mass of the quantum dot toluene solution, 2 parts by mass of methacrylic acid-modified silicone oil X-32-3817-3 (Shin-Etsu Chemical Co., Ltd.) were added. After stirring, mixing, and degassing, the solution was irradiated with a UV-LED at a wavelength of 365 nm and an output power of 4000 mW / cm² while stirring. 2 The light was applied for 20 seconds. After the reaction, ethanol was added for precipitation. After centrifugation, the supernatant was removed, and the mixture was dispersed again in toluene to obtain a composition containing quantum dots. The emission wavelength, half-width at half-maximum (WHM), and fluorescence efficiency (internal quantum efficiency) of the quantum dots were measured. The results showed an emission wavelength of 533 nm, a WHM of 40 nm, and an internal efficiency of 69%.
[0068] (Manufacturing method of wavelength conversion materials) Wavelength conversion materials were prepared using the obtained quantum dot-rich composition. 1.0 g of a 1.0% by mass toluene solution of the quantum dot-rich polymer was mixed with 10.0 g of silicone resin (LPS-5547 prepared by Shin-Etsu Chemical Co., Ltd.). The mixture was heated to 60°C while stirring, and the solvent was removed under reduced pressure. Then, the mixture was degassed under vacuum and coated onto a 50 μm thick polyethylene terephthalate (PET) film. A 100 μm thick semiconductor nanoparticle resin layer was formed using a rod coater. The PET film was then laminated onto this resin layer. The film was heated at 60°C for 2 hours and then at 150°C for 4 hours to cure the semiconductor nanoparticle resin layer, thus preparing the wavelength conversion material. Observation of the prepared wavelength conversion material using an optical microscope confirmed the absence of quantum dot agglomerates, indicating good compatibility between the quantum dots and the resin. The emission wavelength, fluorescence emission half-width at half-maximum (FWHM), and fluorescence efficiency (internal quantum efficiency) of the wavelength conversion material were measured. The results showed that the emission wavelength was 534 nm, the FWHM was 41 nm, and the internal quantum efficiency was 52%.
[0069] (Reliability Testing) The obtained wavelength conversion material was treated at 85°C and 85% RH (relative humidity) for 250 hours, and its reliability was evaluated by measuring the fluorescence efficiency of the treated wavelength conversion material. The emission wavelength, fluorescence half-width at half-maximum (FWHM), and fluorescence efficiency (internal quantum efficiency) of the wavelength conversion material after 250 hours of treatment were measured. The results showed an emission wavelength of 534 nm, a FWHM of 41 nm, and an internal quantum efficiency of 49%. Since the change rate of quantum efficiency measured by the reliability test was approximately 6%, it was confirmed that even in comparative examples, the quantum dots in the wavelength conversion material exhibit high stability when treated on a small scale.
[0070] In Examples 1-5 and Comparative Example 2 described below, the processing volume was increased compared to Comparative Example 1, while the conditions of the surface treatment process were changed, and the same evaluation as Comparative Example 1 was conducted. In Examples 1-5, the following were used... Figure 1 The surface treatment apparatus shown performed quantum dot surface treatment (photopolymerization reaction with silicone oil).
[0071] [Example 1] In the surface treatment step (polymer synthesis of quantum dots), 200 mL of the quantum dot toluene solution (QD concentration 7% by mass) after the ligand exchange step was added to a flask pre-purged with nitrogen. Two parts by mass of methacrylic acid-modified silicone oil X-32-3817-3 (Shin-Etsu Chemical Co., Ltd.) were added relative to 100 parts by mass of the quantum dot toluene solution. Additionally, one part by mass of Irgacure 1173 (IGM resins BV) was added relative to 100 parts by mass of the silicone oil as a photopolymerization initiator. After mixing and degassing, the quantum dots were surface-treated (photopolymerization reaction with silicone oil) using a surface treatment apparatus equipped with a UV-LED irradiation device and a quartz tube with a 2 mm diameter and a 120 mm irradiation area. The transmittance of the quartz tube at this time was 0.4%. The solution was pressurized using nitrogen gas to flow at a rate of 5 mL / min, while a UV-LED irradiation device was used to irradiate the solution at a wavelength of 365 nm and an output power of 500 mW / cm². 2 After the reaction was complete, ethanol was added for precipitation. After centrifugation, the supernatant was removed and redispersed in toluene to obtain a polymer containing ions.
[0072] [Example 2] In the surface treatment step (polymer synthesis of quantum dots), 200 mL of the quantum dot toluene solution (QD concentration 8% by mass) after the ligand exchange step was added to a flask pre-purged with nitrogen. Two parts by mass of methacrylic acid-modified silicone oil X-32-3817-3 (Shin-Etsu Chemical Co., Ltd.) were added relative to 100 parts by mass of the quantum dot toluene solution. Additionally, one part by mass of Irgacure 1173 (IGM resins BV) was added relative to 100 parts by mass of the silicone oil as a photopolymerization initiator. After mixing and degassing, the quantum dots were surface-treated (photopolymerization reaction with silicone oil) using a surface treatment apparatus equipped with a UV-LED irradiation device and a quartz tube with a 2 mm diameter and a 120 mm irradiation area. The transmittance of the quartz tube at this time was 0.1%. The solution was pressurized using nitrogen gas to flow at a rate of 5 mL / min, while a UV-LED irradiation device was used to irradiate the solution at a wavelength of 365 nm and an output power of 500 mW / cm². 2 After the reaction was complete, ethanol was added for precipitation. After centrifugation, the supernatant was removed and redispersed in toluene to obtain a polymer containing ions.
[0073] [Example 3] In the surface treatment step (polymer synthesis of quantum dots), 200 mL of the quantum dot toluene solution (QD concentration 7% by mass) after the ligand exchange step was added to a flask pre-purged with nitrogen. Additionally, 2 parts by mass of methacrylic acid-modified silicone oil X-32-3817-3 (Shin-Etsu Chemical Co., Ltd.) were added to 100 parts by mass of the quantum dot toluene solution. Furthermore, 1 part by mass of Irgacure 1173 (IGMresins BV) was added to another flask pre-purged with nitrogen as a photopolymerization initiator, relative to 100 parts by mass of the silicone oil. After stirring, mixing, and degassing, the quantum dots were surface-treated (photopolymerization reaction with silicone oil) using a surface treatment apparatus equipped with a UV-LED irradiation device, a quartz tube with a 2 mm diameter and a 120 mm irradiation area, and a mixing section for the mixed solution. At this point, the transmittance of the quartz tube was 0.4%. The quantum dot solution was pressurized with nitrogen gas at a flow rate of 5 mL / min, and the silicone oil was flowed at a flow rate of 0.1 mL / min. The two solutions were mixed using a mixer in the pipeline and then delivered to the light irradiation area. A UV-LED irradiation device was used to irradiate the area at a wavelength of 365 nm and an output power of 500 mW / cm². 2 After the reaction was complete, ethanol was added for precipitation. After centrifugation, the supernatant was removed and redispersed in toluene to obtain a polymer containing ions.
[0074] [Comparative Example 2] In the surface treatment step (polymer synthesis of quantum dots), 200 mL of the quantum dot toluene solution (QD concentration 7% by mass) after the ligand exchange step was added to a flask pre-purged with nitrogen. Two parts by mass of methacrylic acid-modified silicone oil X-32-3817-3 (Shin-Etsu Chemical Co., Ltd.) were added relative to 100 parts by mass of the quantum dot toluene solution. Additionally, one part by mass of Irgacure1173 (IGM resins BV) was added relative to 100 parts by mass of the silicone oil as a photopolymerization initiator. After stirring, mixing, and degassing, the solution was irradiated with a UV-LED at a wavelength of 365 nm and an output power of 4000 mW / cm² while stirring. 2 The light was applied for 200 seconds. After the reaction was complete, ethanol was added for precipitation. After centrifugation, the supernatant was removed and redispersed in toluene to obtain a polymer containing ions.
[0075] [Example 4] In the surface treatment step (polymer synthesis of quantum dots), 200 mL of the quantum dot toluene solution (QD concentration 7% by mass) after the ligand exchange step was added to a flask pre-purged with nitrogen. Two parts by mass of methacrylic acid-modified silicone oil X-32-3817-3 (Shin-Etsu Chemical Co., Ltd.) were added relative to 100 parts by mass of the quantum dot toluene solution. Additionally, one part by mass of Irgacure 1173 (IGM resins BV) was added relative to 100 parts by mass of the silicone oil as a photopolymerization initiator. After stirring, mixing, and degassing, the quantum dots were surface-treated (photopolymerization reaction with silicone oil) using a surface treatment apparatus equipped with a UV-LED irradiation device and a quartz tube with a 3 mm diameter and a 120 mm irradiation area. The transmittance of the quartz tube at this time was 0.02%. The solution was pressurized using nitrogen gas to flow at a rate of 5 mL / min, while a UV-LED irradiation device was used to irradiate the solution at a wavelength of 365 nm and an output power of 500 mW / cm². 2 After the reaction was complete, ethanol was added for precipitation. After centrifugation, the supernatant was removed and redispersed in toluene to obtain a polymer containing ions.
[0076] [Example 5] In the surface treatment step (polymer synthesis of quantum dots), 200 mL of the quantum dot toluene solution (QD concentration 10% by mass) after the ligand exchange step was added to a flask pre-purged with nitrogen. Two parts by mass of methacrylic acid-modified silicone oil X-32-3817-3 (Shin-Etsu Chemical Co., Ltd.) were added relative to 100 parts by mass of the quantum dot toluene solution. Additionally, one part by mass of Irgacure 1173 (IGM resins B.V.) was added relative to 100 parts by mass of the silicone oil as a photopolymerization initiator. After stirring, mixing, and degassing, the surface treatment of the quantum dots (photopolymerization reaction with silicone oil) was performed using a reaction apparatus equipped with a UV-LED irradiation device and a quartz tube with a pipe diameter of 2 mm and an irradiation area of 120 mm. At this time, the transmittance of the quartz tube was 0.04%. The solution was pressurized using nitrogen gas to flow at a rate of 5 mL / min, while a UV-LED irradiation device was used to irradiate the solution at a wavelength of 365 nm and an output power of 500 mW / cm². 2 After the reaction was complete, ethanol was added for precipitation. After centrifugation, the supernatant was removed and redispersed in toluene to obtain a polymer containing ions.
[0077] Wavelength conversion materials were prepared using the polymers with sub-dot content obtained in Examples 1-5 and Comparative Example 2. 1.0 g of a 1.0% by mass toluene solution of the polymer with sub-dot content was mixed with 10.0 g of silicone resin (prepared by Shin-Etsu Chemical Co., Ltd. as LPS-5547). The mixture was heated at 60°C while stirring, and the solvent was removed under reduced pressure. Then, the mixture was degassed under vacuum and coated onto a 50 μm thick polyethylene terephthalate (PET) film. A 100 μm thick semiconductor nanoparticle resin layer was formed using a rod coater. The PET film was then laminated onto this resin layer. The film was heated at 60°C for 2 hours and then at 150°C for 4 hours to cure the semiconductor nanoparticle resin layer, thereby preparing the wavelength conversion material.
[0078] The obtained wavelength conversion material was treated at 85°C and 85% RH (relative humidity) for 250 hours, and its reliability was evaluated by measuring the fluorescence efficiency of the treated wavelength conversion material.
[0079] Table 1 shows the surface treatment conditions, quantum dots, and fluorescence luminescence efficiency after fabrication of wavelength conversion materials in Examples 1-5 and Comparative Examples 1 and 2, as well as the values of fluorescence luminescence efficiency after reliability evaluation.
[0080] [Table 1] *Any cohesion? ○ (None), △ (Less), × (More)
[0081] As shown in Table 1, it can be seen that in Comparative Example 2, the internal quantum efficiency was significantly reduced during the preparation of the wavelength conversion material, and the emission wavelength and long-wavelength shift were both large. Microscopic observation revealed a greater number of condensates around 10–50 μm in Comparative Example 2, which can be attributed to the reduced internal quantum efficiency.
[0082] On the other hand, no aggregates were observed in Examples 1-3, suggesting that the decrease in internal quantum efficiency was suppressed. Only a small amount of aggregates were observed in Examples 4 and 5, which was less than in Comparative Example 2, indicating that the decrease in internal quantum efficiency and the long-wavelength shift of the emission wavelength were suppressed. Therefore, in Examples 1-5, by stably covering the silicone compound, compatibility with the resin was improved and aggregation was effectively suppressed.
[0083] Furthermore, a comparison of the reliability test results (85°C, 85% RH, 250-hour treatment) showed that the stability of Examples 1-5 was improved compared to Comparative Example 2. In particular, it can be considered that in Examples 1-3, where the light transmittance of the quartz tube during surface treatment was 0.1% or higher, the decrease in internal quantum efficiency was suppressed to below 10%, and quantum dots with properties equivalent to those of the small-scale treatment of Comparative Example 1 could be obtained.
[0084] As described above, it has been confirmed that when processing the surface of quantum dots covered with organosilicon compounds, as in Examples 1-5, by allowing the solution to flow through a reaction channel made of a light-transmitting material while conducting a photopolymerization reaction, even with an increased amount of quantum dot solution being processed, the quantum dots covered with organosilicon compounds after surface treatment exhibit high stability, and the degradation of fluorescence luminescence efficiency under high temperature and high humidity conditions using the wavelength conversion material of these quantum dots is suppressed, resulting in high reliability.
[0085] Furthermore, the present invention is not limited to the above-described embodiments. The above embodiments are illustrative examples, and any technical solutions that have substantially the same composition and perform the same effects as the technical concept described in the claims of the present invention are included within the technical scope of the present invention.
Claims
1. A surface treatment method for quantum dots, characterized in that, A solution of ligands containing coordinating and reactive substituents, along with quantum dots with the coordinating substituents located on the surface and an organosilicon compound, is continuously supplied to a reaction channel made of a light-transmitting material. Simultaneously, the reaction channel is irradiated with light, causing the organosilicon compound to undergo a photopolymerization reaction with the reactive substituents, thereby coating the surface of the quantum dots with the organosilicon compound. The reaction channel is tubular. The concentration of the solution and / or the diameter of the reaction conduit are adjusted in such a way that the transmittance of the light transmitted to the reaction conduit is at least 0.1%.
2. The surface treatment method for quantum dots according to claim 1, characterized in that, The coordinating substituent is any one or more of amino, thiol, carboxyl, phosphine, and quaternary ammonium salts.
3. The surface treatment method for quantum dots according to claim 1, characterized in that, The reactive substituent is any one or more of vinyl, acryloyl, methacryloyl, thiol, epoxy, and oxetane.
4. The surface treatment method for quantum dots according to claim 2, characterized in that, The reactive substituent is any one or more of vinyl, acryloyl, methacryloyl, thiol, epoxy, and oxetane.
Citation Information
Patent Citations
Immunoassay
JP1978056318A
Control system in common use between series
JP1984000720A
Quantum dot film, lighting device, and lighting method
JP2013544018A
Quantum dot dispersion and self-luminous photosensitive resin composition comprising the same, and color filter and image display device manufactured using the composition
JP2017021322A
Surface-functionalized nanoparticles
CN102272217A
